Determinant of career intention in Malaysia hospitality industry for hearing disabled youth - Mat Yusoff, Norhayati; Ungku Zainal Abidin, Ungku Fatimah; Mohamad, Siti Fatimah; Wan Abdullah, Wan Arnidawati; Alias, Roslinda; Sudono, Agus (e-IPH, 2024)
This study examined the association between the determinants influencing the career intention of students with hearing disabilities in the hospitality industry. Data were collected from 175 students with hearing disabilities who enrolled in Certificates in Hotel and Catering, Basic Culinary, and Basic Pastry at Polytechnic and Community Colleges (n=4) in Malaysia. Questionnaires were developed and distributed via face to face with the help of a sign language translator. The findings revealed that perceived industry characteristics (r=0.611, p < .001) and self-efficacy (r=0.742, p < .001) were strongly related to students with hearing disabilities' career intentions in the hospitality workforce.